AMBER Alert: Best Practices Guide for Broadcasters and Other Media Outlets (2005) - U.S. Department of Justice, Office of Justice Programs, Office of Juvenile Justice and Delinquency Prevention (My University, 2016)
Provides state, regional, and local authorities with the information necessary for developing and improving AMBER Alert initiatives and procedures. (palabras claves: abducción infantil, abducción de niños)